Spatio-temporal evolution of mortality in Cape Verde: 1995-2018. - Domingos Veiga Varela; Maria do Rosário Oliveira Martins; António Furtado; Maria da Luz Lima Mendonça; Ngibo Mubeta Fernandes; Ivone Santos; Edna Duarte Lopes (Public Library of Science (PLoS), 2023)
Located in West Africa, Cabo Verde is a low income country, with significant gains in health indicators. Mortality is an important demographic factor. Its analysis provides essential statistical data for the design, implementation and evaluation of public health programs. The propose of this work is to analyze the spatio-temporal evolution of mortality in Cabo Verde between 1995 to 2018. This is an observational, quantitative study that performs demographic analysis of mortality data from the Ministry of Health of Cabo Verde. Specific mortality rates from standardized causes were calculated considering the population of the country as a reference in the year 2010 and also the standardized rate for all causes on each island, aiming at comparing the islands. During the period under analysis, the number of deaths in men was always higher than that of women. The main causes of death were diseases of the circulatory system and with a higher incidence in women. São Nicolau, Brava, and Santo Antão islands have mortality rates, higher than the national level (2010-2018). The main cause of premature death in women as identified as diseases of the circulatory system, while in men it is injuries, trauma, poisoning and external causes. There was a 72% decrease in the mortality rate due to unclassified symptoms and clinical signs, and an increase in respiratory diseases and tumours. With the exception of diseases of the circulatory system, mortality rates in men are higher than in women for all the considered causes. A decrease in specific mortality rates by age group is expected for both sexes, with a greater gain in men in the younger age groups. With these data, it is intended to alert health decision-makers about the best strategies to be defined in the reduction of mortality in the country.